2012
DOI: 10.1111/j.1440-1843.2011.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical endobronchial ultrasound skills following clinical versus simulation training

Abstract: EBUS-TBNA simulator use leads to rapid acquisition of clinical EBUS-TBNA skills comparable with that obtained with conventional training methods using practice on patients, suggesting that skills learned using an EBUS-TBNA simulator are transferable to clinical EBUS-TBNA performance. EBUS-TBNA simulators show promise for training, potentially minimizing the burden of procedural learning on patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 23 publications
(30 reference statements)
0
66
0
Order By: Relevance
“…Computer bronchoscopy simulators have been validated as a means of measuring bronchoscopic skills [25][26][27] . Other studies have demonstrated the bronchoscopy simulator to be a useful tool for enhancing learning [28][29][30] and improving procedural efficiency [31][32][33] , with effective skill transfer from the simulator to reality [25,31] , with studies now focusing on using these validated instruments to evaluate competency [34,35] . Use of inanimate and animal models for learning bronchoscopy [33] , and the use of simulation-based curricula for learning other medical procedures have also been shown to be effective [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Computer bronchoscopy simulators have been validated as a means of measuring bronchoscopic skills [25][26][27] . Other studies have demonstrated the bronchoscopy simulator to be a useful tool for enhancing learning [28][29][30] and improving procedural efficiency [31][32][33] , with effective skill transfer from the simulator to reality [25,31] , with studies now focusing on using these validated instruments to evaluate competency [34,35] . Use of inanimate and animal models for learning bronchoscopy [33] , and the use of simulation-based curricula for learning other medical procedures have also been shown to be effective [36] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of simulation based bronchoscopy training incorporated additional studies [42]. These studies included animal models, manikins, designed artificial models or VRS bronchoscopy and endobronchial ultrasound training [26,[43][44][45][46][47][48][49]. These studies used various differing models and demonstrated benefits from using simulation for purpose of bronchoscopy training.…”
Section: Vrs Bronchoscopy Studiesmentioning
confidence: 99%
“…As such, trainees can learn in a controlled environment without exposing patients to risks and increasing the burden of procedural training on patients. In a prospective study on a group of pulmonary trainees receiving EBUS training through a simulator versus a second group receiving EBUS training via conventional method on patients, the EBUS simulator led to more rapid acquisition of clinical EBUS skills comparable with those obtained by conventional method 26. Thus, it will be interesting to explore simulation‐based educational programs for EBUS learning as this form of learning has been shown to improve outcomes in other procedural skills, such as thoracentesis,27 central venous catheter insertion,6 and laparoscopic surgery 28.…”
Section: Discussionmentioning
confidence: 99%